SISTEM PROTEKSI SALURAN DISTRIBUSI JARINGAN LISTRIK MENGGUNAKAN ETAP DI PONDOK PESANTREN NURUL JADID STUDI KASUS TRAFO DH 760/160 - Moh. Hambali, Moh. Hambali; Eva Jamiyanti; Sutra Wardatul Jannah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to analyze the electrical power distribution system at the Nurul Jadid Islamic Boarding School, focusing on the DH 760/160 transformer using ETAP (Electrical Transient Analyzer Program) software version 19.01. The protection system applied to the distribution system is the main focus, considering its important role in maintaining the reliability of electricity supply in the Islamic boarding school environment. This study includes three main analyses: power flow (load flow), short circuit disturbances, and voltage drop and power losses. The results of the power flow analysis show that the DH 760/160 transformer has an efficiency of 96.32% in reducing the voltage from 20 kV to 0.4 kV. However, there is an imbalance in the load distribution, with the junior high school branch showing a load reaching 80.93%. Analysis of short faults on the mosque bus and junior high school shows a large potential for damage, with fault currents recorded up to 4,817 kA, indicating the need for increased protection to detect and disconnect faults more quickly. Furthermore, the analysis of voltage drop and power losses showed that the largest losses occurred in the transformer, with losses reaching 2.8 kW and 4.2 kvar, and a voltage drop of 1.16%. Significant voltage drops can affect the efficiency and quality of power received by the load. Overall, although the distribution system is functioning well, this study identified several areas that need improvement, including load regulation, protection system enhancements, and power loss reduction to increase the reliability and efficiency of the electricity distribution system at the Nurul Jadid Islamic Boarding School.